Image et pensée chez les Grecs passées aux filtres des catégories modernes - François Lissarrague; Alain Schnapp; Noémie Hosoi; Vasiliki Zachari (Images Re-Vues)
How did modern thought categorise ancient Greek civilisation? Is the academic separation of history, society, myth, religion, politics, literature and art still viable? More precisely, which of these divisions were observed in vase painting? A book, La Cité des Images: Religion et Société en Grèce Antique, went down in history on iconographical studies. Thanks to the publication and a group of researchers who collaborated on this project, which proposes a new way of perceiving Attic imagery, a new anthropological viewpoint saw the light of day. An interview with François Lissarrague and Alain Schnapp 30 years after the publication of the City of Images was essential for bringing the anthropological approach of Greek images up to date. The discussion led to an open dialogue that explored different approaches of the past, in archaeology, transmission, the necessity of ordering, Jean-Pierre Vernant and Pierre Vidal-Naquet. Focusing on categories, the interview also gave us the opportunity to discuss accomplished projects, such as François Lissarrague’s most recent publication, La Cité des Satyres, as well as work in progress, such as the upcoming exhibition on nature in Greek art. Lastly, the question of categories as a necessary evil to comprehend a research field was present throughout the interview.